The dominant protein phosphatase PP1c isoform in smooth muscle cells, PP1cβ, is essential for smooth muscle contraction - Chang, Audrey N. (J Biol Chem, 2018)
Contractile force development of smooth muscle is controlled by balanced kinase and phosphatase activities toward the myosin regulatory light chain (RLC). Numerous biochemical and pharmacological studies have investigated the specificity and regulatory activity of smooth muscle myosin light-chain phosphatase (MLCP) bound to myosin filaments and comprised of the regulatory myosin phosphatase target subunit 1 (MYPT1) and catalytic protein phosphatase 1cβ (PP1cβ) subunits. Recent physiological and biochemical evidence obtained with smooth muscle tissues from a conditional MYPT1 knockout suggests that a soluble, MYPT1-unbound form of PP1cβ may additionally contribute to myosin RLC dephosphorylation and relaxation of smooth muscle. Using a combination of isoelectric focusing and isoform-specific immunoblotting, we found here that more than 90% of the total PP1c in mouse smooth muscles is the β isoform. Moreover, conditional knockout of PP1cα or PP1cγ in adult smooth muscles did not result in an apparent phenotype in mice up to 6 months of age and did not affect smooth muscle contractions ex vivo. In contrast, smooth muscle–specific conditional PP1cβ knockout decreased contractile force development in bladder, ileal, and aortic tissues and reduced mouse survival. Bladder smooth muscle tissue from WT mice was selectively permeabilized to remove soluble PP1cβ to measure contributions of total (α-toxin treatment) and myosin-bound (Triton X-100 treatment) phosphatase activities toward phosphorylated RLC in myofilaments. Triton X-100 reduced PP1cβ content by 60% and the rate of RLC dephosphorylation by 2-fold. These results are consistent with the selective dephosphorylation of RLC by both MYPT1-bound and -unbound PP1cβ forms in smooth muscle.